Pemanfaatan CMS Prestashop Sebagai Solusi Dagang Di Masa Pandemi Kepada PKK Paras 2610 Perumahan Pabuaran Asri 2 RT 006 RW 010 Cibinong-Bogor - Aulia Paramita; Thomas Afrizal; Han Sulaiman (CV. ALIM'SPUBLISHING, 2024)
The COVID-19 virus pandemic spread throughout the world has had a tremendous impact. Various effects began to emerge from the spread of this virus, causing the global Covid-19 pandemic. Economic activity has decreased and the workforce has increased, those who work in the MSME sector, especially housewives, also feel a big impact, due to the lack of buyers/consumers. Therefore, our community service team wants to provide outreach regarding the use of CMS Prestashop as a trading solution during the pandemic to PKK Paras 2610 Perumahan Pabuaran Asri 2 RT 006 RW 010 Cibinong Bogor. It is hoped that this activity can help PKK mothers, especially those have a small and medium business so that they can gain knowledge about how to utilize technology in trading or running their business and can increase their income better in the future this pandemic